DECISION SUPPORT SYSTEM FOR SCHOLARSHIP IN BALI STATE POLYTECHNIC USING AHP AND TOPSIS - Ni Gusti Ayu Putu Harry Saptarini; Putu Manik Prihatini (Proceeding International Conference on Information Technology and Business, 2015)
One effort to help people in continuing their education is through a scholarship program. Currently there are many scholarship programs from the government and state-owned enterprises or private. With the help of these educational, students race to achieve in order to offset the cost of education which is currently quite expensive. The number of students applying for the scholarship would require a separate time to filter out students who meet the requirements and then rank students based on the criteria of the scholarship. The complexity of the problems occur because each criterion has its own priority. Screening and grading manually would require considerable time and susceptible to human error. This research, developed automatic screening and decision support system to rank students according to given criteria. The method used is analytical hierarchycal process (AHP) to give weight to each criterion based on its priority, and the technique for order of preference by similarity to ideal solution (TOPSIS) to rank students based on its values of each criterion. By construct this decision support system, then selecting scholarship recipients can be faster and valid. The system that was built provide recommendations by rank students based on the final calculation.KEY WORDS: Decision Support System, AHP, TOPSIS, Scholarship.